Cloning, Sequencing and Partial Characterization of the Accessory Gene Region of Plasmid pTC-F14 isolated from the Biomining Bacterium Acidithiobacillus caldus f. - Goldschmidt, Gunther Karl (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MSc (Microbiology))--University of Stellenbosch, 2005.